2020
DOI: 10.1088/1742-6596/1679/2/022066
|View full text |Cite
|
Sign up to set email alerts
|

Observational statistics analysis of seismoelectric effects in a gas condensate reservoir

Abstract: The article considers the observational statistics analysis of seismoelectric effects of the second kind at the Bystryanskoye gas condensate reservoir in Krasnoyarsk Territory. The measurements were carried out by the passive method from 2014 to 2019 on one exploration profile. The authors obtained an averaged profiling curve. Its analysis showed that there exists the repeatability of measurement results, as well as the convergence with the results of mathematical modeling. The collected statistics on the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…As shown in Table 2 , obtained in 2019–2020, the experimental data confirmed the results of the measurements in 2014–2018 [ 27 , 28 , 44 , 45 , 46 , 47 ]. Figure 9 b also shows a curve obtained by solving Equations (1)–(8), according to which the values of the electric field strength E will correspond to the magnitude of the observed SE effect on the day surface.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Table 2 , obtained in 2019–2020, the experimental data confirmed the results of the measurements in 2014–2018 [ 27 , 28 , 44 , 45 , 46 , 47 ]. Figure 9 b also shows a curve obtained by solving Equations (1)–(8), according to which the values of the electric field strength E will correspond to the magnitude of the observed SE effect on the day surface.…”
Section: Resultssupporting
confidence: 84%
“…This was the first attempt to process data obtained in different years of observation. Based on the experience of [ 27 , 28 , 44 , 45 , 46 , 47 ] on this profile, it can be concluded that the amplitude value of the observed cross-correlation coefficient on the Earth’s surface depends on many factors. Thus, the absolute value of this coefficient cannot be used for the assessment, and, therefore, the shape of the resulting curve is a more important factor.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation